Association between maternal diabetes and cardiac left ventricular structure and function in the neonate: a study from the Copenhagen Baby Heart Study. (25th November 2020) - Ghouse, J; Voegg, O; Sillesen, A.S; Pihl, C; Axelsson, A.R; Vejlstrup, N; Oyen, N; Jensen, M.T; Wohlfart, J; Damm, P; Olesen, M.S; Mathiesen, E.R; et al.
Abstract: Background: Prenatal exposure to maternal diabetes has been associated with increased risk of congenital heart defects. Purpose: To evaluate whether maternal diabetes is associated with more subtle morphological and functional cardiac changes in neonates without congenital heart defects. Methods: We included 17, 869 newborns sampled from the Copenhagen Baby Heart Study, all of whom underwent transthoracic echocardiography within 30 days of delivery. We investigated the association between exposure to maternal diabetes (pre-existing diabetes [type 1 or type 2 diabetes] or gestational diabetes [GDM]) and the neonates' echocardiographic indices of left ventricular structure (left posterior wall thickness in end-diastole [LVPWd], interventricular septum thickness in end-diastole [IVSd], left ventricular internal diameter in end-systole [LVIDs] and end-diastole [LVIDd]), systolic function (fractional shortening [FS], stroke volume [SV]) and diastolic function (mitral valve peak early and atrial filling velocities, deceleration time of early filling, and E/A-ratio), using linear and logistic regression. Models were adjusted for maternal age, infant sex, infant birth weight for gestational age and gestational age in days. In additional analyses, we evaluated the relationship between HbA1C levels in first and third trimester and left ventricular structure and function. Results: We found that infants exposed to pre-existing maternal diabetes (n=x) had, on average, a thicker LVPWd (mean difference 0.12 mm [95% CI: 0.06–0.19]), a smaller LVIDs (−0.27 mm [95% CI: −0.46, −0.07]) and LVIDd (−0.43 mm [95% CI: −0.66, −0.19]), and decreased SV (−0.50 ml [95% CI: −0.77, −0.23]). We found no significant differences in IVSd, FS, and measures of diastolic function for infants exposed to pre-existing maternal diabetes compared with infants not exposed to diabetes. Infants exposed to GDM (n=) also had thicker LVPWd (0.06 mm [95% CI: −0.28, −0.01]) and smaller LVIDs (−0.15 mm [95% CI: −0.28, −0.01]); however, on average, IVSd, LVIDd, and measures of systolic and diastolic function did not differ for infants born to mothers with and without GDM. We observed no consistent association between HbA1C levels measured early and late in pregnancy in mothers with diabetes and indices of left ventricular structure and function. Conclusion: In conclusion, we found that exposure to maternal pre-existing diabetes, and to a lesser degree GDM, was associated with changes in neonatal left ventricular structure and function, including a thicker left ventricular posterior wall, smaller left ventricular internal diameters, and lower stroke volumes. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Rigsbospitalet Research Foundation